Kreativitas Guru Pengerak Menuju Penguatan Profil Pelajar Pancasila - Nari, Nola; Suhaili, Neviyarni; Khaidir, Christina (JURNAL KONSELING GUSJIGANG, 2023)
Problems teacher creativity becomes focus necessary problem searched Street out and have becomes problem classics of the world of education. One of them implementation curriculum independent through creative driving teachers  as means strengthening profile Pancasila students. Destination study this is for dig forms creativity that can driving teacher emerged through the driving teacher program and the teaching module as a teacher means strengthening profile Pancasila students. Study this use approach qualitative. Informant study chosen with technique purposive sampling. The data collection process is carried out with interview deep, study documentation and notes field . Data analysis was performed with refer to the Miles and Huberman model. For ensure the validity of the researcher 's data use technique triangulation and upgrade perseverance researcher in analyze document found. Research results show that forms driving teacher creativity is creativity personal form desire for move to do change, creativity process with follow training and creativity product through development teaching module as well creativity form encouragement good from personal or environment as well as government. The creativity of driving teachers will produce strengthening profile Pancasila students